N-Butyl-4-hydroxy-2-methyl-2H-1,2-benzothiazine-3-carboxamide 1,1-dioxide - Ahmad, Matloob (International Union of Crystallography, 2008)
The title compound, C(14)H(18)N(2)O(4)S, contains hydrogen-bonded dimeric pairs of molecules arranged around inversion centers, forming 14-membered rings with an R (2) (2)(14) motif. The structure is stabilized by extensive intramolecular interactions. The thiazine ring adopts a half-chair conformation, with the S and N atoms displaced by −0.485 (3) and 0.296 (3) Å, respectively, from the plane formed by the remaining atoms of the ring.